Evaluation and Preparation of a Designed Kartogenin Drug Delivery System (DDS) of Hydrazone-Linkage-Based pH Responsive mPEG-Hz-b-PCL Nanomicelles for Treatment of Osteoarthritis - Su, Wen-Ta; Huang, Ching-Cheng; Liu, Hsia-Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA) is a chronic disease caused by the damage of articular cartilage. Kartogenin (KGN), a small heterocyclic molecule, has been described to effectively enhance the chondrogenic differentiation of human bone marrow MSC (hBMSC), exhibit chondroprotective effects in vitro and reduce cartilage degeneration after intra-articular injection in OA mouse models. Nano-level microcells could be a suitable drug carrier technology for the treatments. The acid-base responsive methoxy poly(ethylene oxide)-hydrazone-poly(ε-caprolactone) (mPEG-Hz-PCL) copolymers was synthesized via sequential ring-opening polymerization (ROP). The structure was characterized by 1H NMR. Micelles loaded with KGN can be swallowed by chondrocytes after intra-articular in-jection, and released after the disintegration of the slightly acidic environment in the organelles. At the same time, it can achieve cartilage hyperplasia and anti-inflammatory effects. An in vitro OA like chondrocyte model was established using IL 1β stimulated human SW 1353 chondrocytes. Cell viability was assessed using an MTT assay.